Homeward bound II :lost in San Francisco - Hays, Robert, 1947-; Greist, Kim. (Burbank, Calif. : Walt Disney Home Video ; Boston, Mass. : DVS Home Video, 1994)
Homeward Bound: A fun-loving bulldog, a wise old golden retriever, and a hilarious Himalayan cat travel through the rugged Sierras in a search for their missing human family.
Homeward bound II: When Chance, the American bulldog; Sassy, the Himalayan cat; and Shadow, the golden retriever accidentally get separated from their vacationing owners, the pets navigate the streets of San Francisco, trying to find their home across the Golden Gate Bridge.
Homeward Bound II is in the widescreen format.
Closed captioned for the hearing impaired.
Rated G.
Homeward Bound: director, Duwayne Dunham ; producers, Franklin R. Levy & Jeffrey Chernov ; screenplay, Caroline Thompson & Linda Woolverton ; based upon the novel "The incredible journey" by Sheila Burnford ; Homeward bound II : director, David R. Ellis ; produced by Barry Jossen ; written by Chris Hauty and Julie Hickson.
Robert Hays, Kim Greist.
Keywords: Animal films; Dogs -- Drama; Cats -- Drama; Films for the hearing impaired